(untitled) (Islas, 2021)
Armando Hart, consecuente y convencido revolucionario martiano y marxista, desarrolló un accionar y un pensamiento comprometido con la humanidad y el desarrollo social, inmerso en la lucha por alcanzar y mantener la soberanía nacional y la construcción de una sociedad de igualdad y justicia social. El objetivo de este trabajo es llamar la atención y convocar a estudios que permitan definir el aporte de este intelectual cubano a la construcción de las ideas en Cuba y las aristas que reveló como esenciales en el constructo teórico nacional. Este texto propone aproximaciones a las ideas de Hart sobre el marxismo como teoría científica para la interpretación de la realidad social destacando su universalidad, alcance y trascendencia para interpretar y transformar varios contextos, entre ellos el cubano. Abstract: Armando Hart, consistent and convinced martiano and Marxist revolutionary, developed an action and a thought committed to humanity and social development, immersed in the struggle to achieve and maintain national sovereignty and the construction of a society of equality and social justice. The objective of this paper is to draw attention and to invite to study to define the contribution of this Cuban intellectual to the construction of ideas in Cuba and the different aspects revealed as essential in the national theoretical construct. This text proposes approaches to Hart’s ideas about Marxism as a scientific theory for the interpretation of social reality, highlighting its universality, scope, and transcendence for interpreting and transforming various contexts, including Cuban. Keywords: Armando Hart Dávalos’s ideas about Marxism; Marxism as scientific theory; interpretation of social reality